Analisis Persepsi dan Biaya Transaksi Terhadap Sumber Kredit Usaha Pengolahan Ikan Asin - Nurul Maulina; Dwi Rachmina; Suprehatin Suprehatin (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2021)
The growth and development of MSMEs are hampered due to capital constraints, so that MSMEs need other sources of capital to meet their business needs, one of which is with credit. In Muara Angke Traditional Fisheries Processing (PHPT) there are formal and informal credit institutions. The decision-making process of which credit institution will be chosen is determined by the processor's perception of the two institutions, where each institution will incur different transaction costs incurred by salted fish processors. The purpose of this study was to analyze the perceptions of salted fish processors on credit institutions and the amount of credit transaction costs incurred. The perceptual analysis uses the importance-performance analysis method and transaction costs are calculated using the transaction cost analysis method. The total sample of 72 salted fish processing business units in PHPT Muara Angke. The results showed that based on the criteria of processing perceptions of formal institutions better. This is indicated by the measurement of the average value of formal interests 4,48, the average value of the performance of formal institutions is 4,04 while the average value of the interests of non-formal institutions is 4,16 and the average value of the performance of non-formal institutions is 3,99. However, the transaction costs per loan period that must be issued by processors with formal credit (Rp 126.750) are greater than the transaction costs incurred by processors with non-formal credit (Rp 15.434). The largest transaction cost component informal credit is implementation costs (62,60 per cent), while informal credit is information costs (36,37 per cent).